Racial/ethnic differences in the associations between social support and cardiovascular morbidity and mortality in the Multi-Ethnic Study of Atherosclerosis (MESA) - Jeanean B. Naqvi; Taynara Formagini; Matthew A. Allison; Namratha R. Kandula; Jee Won Park; Britta A. Larsen (BMC Public Health)
Abstract Background Despite the established link between social support and cardiovascular disease (CVD) outcomes, few studies have examined racial/ethnic variation in these associations. This study utilized data from the Multi-Ethnic Study of Atherosclerosis (MESA) to investigate racial/ethnic differences in perceived social support and in the link between support and incident hard CVD events and mortality. Method Participants (N = 6,814) were 45–84 years of age who identified as White, Black, Hispanic/Latino, or Chinese without known clinical CVD at baseline (2000–2002). Racial/ethnic differences in perceived support (overall, emotional, informational, and instrumental) were tested using multiple regression with adjustments for demographic, socioeconomic, lifestyle/psychosocial, and clinical risk factors, and immigration history. Racial/ethnic differences in the association between perceived support and incident CVD events or mortality were tested using Cox proportional hazards models with progressive adjustments for the same covariates. Results At baseline, the mean age was 62.15 years (SD = 10.23); 38.5% identified as White, 27.8% as Black, 22.0% as Hispanic/Latino, and 11.8% as Chinese. Black and Hispanic/Latino participants reported higher levels of overall support, emotional support, and informational support than White participants (p’s < 0.05). Chinese participants reported less informational support (p = .010) than White participants. Higher informational support was associated with decreased risk for hard CVD events. This association did not differ by race/ethnic group. Conclusion Despite racial/ethnic differences in perceptions of support, perceived informational support was protective against CVD for participants of all racial/ethnic backgrounds.